1986
DOI: 10.1073/pnas.83.6.1926
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Mycobacterium leprae genes from a Streptococcus mutans promoter in Escherichia coli K-12.

Abstract: Genomic libraries of Mycobacterium leprae DNA partially digested with Pst I were constructed in the expression vector pYA626, which contains the promoter region from the Streptococcus mutans gene encoding aspartate asemialdehyde dehydrogenase, which is very efficiently expressed in Escherichia coli. We have detected several clones that complement a mutation in the citrate synthase gene of E. coli. Southern blot analysis demonstrated that the complementing DNA was M. leprae DNA. Sodium dodecyl sulfate/polyacryl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
28
0

Year Published

1986
1986
1998
1998

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 19 publications
2
28
0
Order By: Relevance
“…The main reasons for this lack of information are the slow growth rate of the organism, poorly developed gene transfer systems and very little understanding of the genetic being made to the mechanisms of gene regulation in mYcobacteria* It has been shown that mYc0-bacterial promoters function poorly in Escherichia COli (Bashyam et al-9 1996 ;Clark-Curtiss et al7 1985 ; Das number of mycobacterial metabolic genes have been cloned by complementation of the mutational defects in the corresponding genes of E. coli (Anderson et al, 1993;Garbe et al, 1990;Jacobs et al, 1986;Stelandre et al, 1992) and mycobacteria (Hinshelwood & Stoker, 1992), very little is known about the regulatory mechanisms involved. More studies are needed to understand the basic features of the regulation of mycobacterial gene expression.…”
Section: Introductionmentioning
confidence: 99%
“…The main reasons for this lack of information are the slow growth rate of the organism, poorly developed gene transfer systems and very little understanding of the genetic being made to the mechanisms of gene regulation in mYcobacteria* It has been shown that mYc0-bacterial promoters function poorly in Escherichia COli (Bashyam et al-9 1996 ;Clark-Curtiss et al7 1985 ; Das number of mycobacterial metabolic genes have been cloned by complementation of the mutational defects in the corresponding genes of E. coli (Anderson et al, 1993;Garbe et al, 1990;Jacobs et al, 1986;Stelandre et al, 1992) and mycobacteria (Hinshelwood & Stoker, 1992), very little is known about the regulatory mechanisms involved. More studies are needed to understand the basic features of the regulation of mycobacterial gene expression.…”
Section: Introductionmentioning
confidence: 99%
“…As many mycobacterial genes are expressed poorly in E. coli (27,57), DNA hybridization was used to search for a recA-like gene from M. tuberculosis rather than screening by functional complementation. The ability of this gene, expressed from a plasmid lac promoter, to complement the different functions of RecA in E. coli strains with various recA alleles has been investigated.…”
mentioning
confidence: 99%
“…It was Shep's policy to retain a few strains of M. leprae by serial passage in mice, particularly as «standard» strains for drug testing. Some of these had been serially passaged in mice for [16][17][18][19][20][21][22][23][24] years , without any detectable change in pathogenicity or growth patterns in mice . Fi nally the stability and survival of M. leprae outside the body was assessed using the foot-pad model, on bacilli recovered from dried nasal discharges.…”
Section: His Career Research Interests and Achievementsmentioning
confidence: 99%
“…From then onwards a series of rapidly advancing technical publications by Roy & Josephine Curtiss and colleagues (19,22) have resulted on the specific genome size of M. leprae distinguishing it from other species of mycobacteria as well as genomic libraries of M. leprae resulting basically using E coli K-12 as the host vec tor. It is pleasing to see that one of these publications (22) is dedicated to Shepard .…”
mentioning
confidence: 99%